Due Dilligence of Enteprises Concerning Respect of Human Rights Under Directive 2024/1760 - Skupień, Dagmara (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
Economic activity which respects human rights and the environment is an ideal that international organizations, such as the UN and the ILO, aim to make a reality. In recent years, the issue of sustainable development has become of particular interest for the European Union. This article focuses on companies' obligations to protect human rights in the sphere of work, covered by the subject of EU Directive 2024/1760, and the consequences of non-compliance with these obligations. In particular, the catalogue of human rights in labour relations which are the subject of protection in this Directive is analysed.